2023
DOI: 10.7759/cureus.46767
|View full text |Cite
|
Sign up to set email alerts
|

The Real DAPSI: A Real-World Retrospective Study on Assessing the Efficacy and Safety of a Fixed-Dose Combination of Dapagliflozin and Sitagliptin in the Indian Population

Rana Bhattacharjee,
Madhukar Rai,
Priyanka Joshi
et al.

Abstract: IntroductionType 2 diabetes mellitus (T2DM) is a chronic metabolic disorder affecting millions of individuals worldwide. Effective management of T2DM is crucial to prevent complications. Dapagliflozin and sitagliptin are oral anti-diabetic agents that have been shown to provide synergistic effects in controlling blood glucose levels. However, there is limited data on the efficacy and safety of the dapagliflozin-sitagliptin fixed-dose combination (FDC) in the Indian population. This study aimed to evaluate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Additionally, a 24-week study revealed that adding dapagliflozin to sitagliptin significantly reduced HbA1c levels compared to placebo, alongside weight reduction and fasting plasma glucose improvements. The clinical evidence supports the efficacy of the sitagliptin and dapagliflozin combination in enhancing key glycaemic parameters and overall patient outcomes [1,4,25].…”
Section: Sub-group Analysesmentioning
confidence: 64%
See 1 more Smart Citation
“…Additionally, a 24-week study revealed that adding dapagliflozin to sitagliptin significantly reduced HbA1c levels compared to placebo, alongside weight reduction and fasting plasma glucose improvements. The clinical evidence supports the efficacy of the sitagliptin and dapagliflozin combination in enhancing key glycaemic parameters and overall patient outcomes [1,4,25].…”
Section: Sub-group Analysesmentioning
confidence: 64%
“…Uncontrolled diabetes poses severe long-term complications such as cardiovascular disease, retinopathy, neuropathy, and nephropathy, emphasizing the importance of timely and comprehensive management to prevent adverse outcomes and enhance quality of life. As the prevalence of T2DM continues to rise globally, there is a growing emphasis on personalized treatment approaches that not only target glycaemic control but also address individual risk profiles and comorbidities to optimize patient outcomes [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the current survey clinicians recommended the FDC therapy with sitagliptin and dapagliflozin for patients initially diagnosed with an HbA1c level of 8%. A real-world retrospective study revealed that the dapagliflozin and sitagliptin FDC significantly contributed to a decrease in HbA1c levels from 8.9 to 7.2 in individuals with T2DM in the Indian population, thereby affirming the safety and efficacy of this combination [11] . According to Bhattacharyya et al, a real-world study conducted in India, a once-daily FDC of dapagliflozin and sitagliptin significantly improves glycemic parameters, such as average daily glucose, time in target, and time above the target, in Indian patients with T2DM at the end of 15 days [10] .…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, they have also been shown to improve both insulin resistance and beta cell function [16] . Bhattacharjee et al found that the combination of dapagliflozin and sitagliptin is effective and safe in reducing BMI among Indian patients with T2DM [11] . [17] .…”
Section: Discussionmentioning
confidence: 99%